PERSEPSI MASYARAKAT TERHADAP PEMBAYARAN DIGITAL PADA TRANSPORTASI UMUM - Al Jabar, Haddid (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2023)
Public transportation is just one area where the development of digital technology has had an impact. Digital payments for public transportation are currently gaining popularity and are widely used by the general public. Nonetheless, the public view of computerized public transportation installments actually needs further review. The purpose of this study is to investigate public perceptions of digital payments for public transportation. The strategy utilized was an internetbased review of 150 respondents who utilized advanced installments on open transportation.